2018
DOI: 10.1073/pnas.1611617114
|View full text |Cite
|
Sign up to set email alerts
|

Metaanalysis of the relationship between violent video game play and physical aggression over time

Abstract: To clarify and quantify the influence of video game violence (VGV) on aggressive behavior, we conducted a metaanalysis of all prospective studies to date that assessed the relation between exposure to VGV and subsequent overt physical aggression. The search strategy identified 24 studies with over 17,000 participants and time lags ranging from 3 months to 4 years. The samples comprised various nationalities and ethnicities with mean ages from 9 to 19 years. For each study we obtained the standardized regressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
119
2
15

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 230 publications
(167 citation statements)
references
References 47 publications
4
119
2
15
Order By: Relevance
“…Further, the American Psychological Association has concluded that video games influence aggression, but not violence (Calvert et al, 2017), although this report has itself come under critical scrutiny by outside scholars (Elson et al, 2019). Prescott et al, (2018) and Anderson et al, (2010) do find correlations between self-reports of aggressive behavior and VVGs over time, although the magnitude of such correlations are very small. As such, additional research needs to be conducted, ideally with preregistered hypotheses, in order to fully explicate the relationship between VVGs and aggression.…”
Section: Violent Video Gamesmentioning
confidence: 88%
“…Further, the American Psychological Association has concluded that video games influence aggression, but not violence (Calvert et al, 2017), although this report has itself come under critical scrutiny by outside scholars (Elson et al, 2019). Prescott et al, (2018) and Anderson et al, (2010) do find correlations between self-reports of aggressive behavior and VVGs over time, although the magnitude of such correlations are very small. As such, additional research needs to be conducted, ideally with preregistered hypotheses, in order to fully explicate the relationship between VVGs and aggression.…”
Section: Violent Video Gamesmentioning
confidence: 88%
“…Despite of the differences in opinion with regard to exposure to mature media and violent behavior, Hull, Brunelle, Prescott, and Sargent have demonstrated a correlation between exposure to violent video games, and violent behavior and aggression over time . Stone and Brucato have also proposed that exposure to violence does not “create” violent individuals, but it may desensitize and perhaps serve to disinhibit a portion of the population that is already predisposed to violent behavior.…”
Section: Discussionmentioning
confidence: 99%
“…The players’ hostility toward women is seen as a part of the homosocial experiences of online video gaming for male players (McInroy & Mishna, ), and a reflection of the aggressive content and context. Indeed, some meta‐analytical findings indicated that violent video game content led to increased aggression and hostility in players (Anderson et al, ; Greitemeyer & Mugge, ) and over time according to longitudinal studies (Prescott, Sargent, & Hull, ). It needs to be noted, though, that other meta‐analyses found relatively weak support for this assumption (Ferguson, ; Sherry, ), or proposed more complex processes, including selection effects (Breuer, Vogelgesang, Quandt, & Festl, ).…”
Section: Online Video Games and Aggressionmentioning
confidence: 99%